Effects Of Leaf Surface Characteristics And Spray Droplets On Effectiveness Of Selected Glyphosate Formulations - Ngah, Norhayati (2010)

(untitled)
Laboratory and glasshouse studies were conducted to examine the effect of leaf surfaces and spray droplets on the effectiveness of glyphosate on some selected plants. The broad leaves plants selected were Diodia ocimifolia, Borreria latifolia, Clidemia hirta, Cleome rutidosperma, Mikania micrantha and Asystasia gangetica, while the narrow leaves consisted of Eleusine indica, Imperata cylindrica, Cyperus kylingia, Axonopus compressus, Pennisetum polistachyon and Paspalum conjugatum. The deposition of pesticide depends on the morphology of leaf surface, thus the leaf surface roughness and epicuticular wax were evaluated. The plants were categorized accordingly to the different type of roughness based on the estimation of three roughness parameters Ra (arithmetic average height parameter), Rq (root-mean-square roughness parameter corresponding to Ra), and Rz (average of high peaks and low valleys over the evaluation length). The leaf was examined by using scanning electron microscopy for the surface roughness while the epicuticular wax content of the leaf was extracted by using chloroform. The amount of wax extracted from the plants varied between species. For broad leaves plant, M. micrantha (44.22μgcm-2) contained the highest quantity of wax. Clidemia hirta (24.03μgcm-2) and A. gangetica (23.03μgcm-2) were grouped in the plant with medium quantity of wax while C. rutidosperma (16.52μgcm-2), B. latifolia (14.19μgcm-2) and D. ocimifolia (10.75μgcm-2) were grouped in plant with low quantity of cuticular wax weight. For narrow leaves plant, E. indica (44.23μgcm-2) and I. cylindrica (49.88μgcm-2) have the highest quantity of wax. Pennisetum polystachion (32.16μgcm-2) and C. kylingia (22.85μgcm-2) were categorized under the plant with medium quantity of wax whereas P. conjugatum (19.59μgcm-2) and A. compressus (16.78μgcm-2) were categorized with low quantity of wax. The wax on the abaxial and adaxial leaf surface of the broad leaves plants was found to be significantly different. In contrast, the amount of wax on the abaxial and adaxial leaf surface of the narrow leaves plants was more or less similar. For the leaf surface roughness of the broad leaves species, B. latifolia were categorized as the roughest followed by C. hirta, D. ocimifolia, A. gangetica, and C. rutidosperma. Mikania micrantha had the smoothest leaf surface among the broad leaves species. On the other hand, the narrow leaves of P. polistachyon were identified as the roughest followed by I. cylindrica and P. conjugatum while E. indica, A. compressus and C. kylingia were categorized in the smoothest surface.